The Collaborative Role of Dentists and Dental Assistants in Treatment Planning: A Systematic Review of Strategies for Optimizing Patient Outcomes - Maha Abdulaziz Almutairi,; layali Saad alshreef,; Afnan Talal Alghunayman,; Hana Ahmed Altunisi,; Yasmin Mohameed Milibary,; Maha Abdullah Algaidi,; Noha Mohammad Aleranei,; Reem Suliman Alharbi, (The Bioscan, 2025)
Objective: This systematic review investigates the collaborative role of dentists and dental assistants in developing and implementing treatment plans and how such collaboration affects patient outcomes. Methods: A systematic search was conducted across databases including PubMed, Scopus, Web of Science, and Cochrane Library for peer-reviewed studies published between 2016 and 2024. Inclusion criteria were studies focusing on teamwork, communication, and collaboration between dentists and dental assistants and their effect on treatment outcomes. Results: Out of 3,150 initial articles, 42 met the inclusion criteria. The review found that coordinated teamwork led to improved diagnostic accuracy, efficiency in treatment delivery, enhanced patient satisfaction, and reduced procedural errors. Communication, clear role definition, and continuing professional development emerged as key enablers. Conclusion: The collaborative dynamics between dentists and dental assistants significantly contribute to improved treatment planning and patient care. Formalized teamwork training and structured communication protocols are recommended for optimized practice.